Microcatheter retrieval device for intravascular foreign body removal. - Smith, T P; Graves, V B; Halbach, V V; Higashida, R T; Fraser, K W; Dowd, C F; Hieshima, G B (American Journal of Neuroradiology, 1993)
A microcatheter foreign body retrieval device is described and its first two clinical applications are presented. The device functions identically to larger loop snare retrievers. It permits access to small vessels and was successful in its first clinical applications.